IMPORTANCE OF MENTAL HEALTH DURING COVID CRISIS: A DESCRIPTIVE STUDY - Jeetika Duggal; Manu Bhai Gaur (International Journal of Ayurveda and Pharma Research, 2020)
The global pandemic of Coronavirus (COVID-19), also termed as health emergency affecting nearly 210 countries and territories has led to negative emotions of fear and agony in the general population. The healthcare regulators and the governments have imposed emergencies and lockdowns in their countries which has led to an adverse effect on the mental health of general public ultimately leading to a rise in anxiety, depression, and associated mental illness. The fear and rising COVID-19 crisis is putting extreme limitations on our finite resources. This report aims to improve status of mental health altered as a result of pandemic, emphasizing to help the general public, mitigate the negative emotions to improve the general wellbeing in this detached period of isolation. With no standard treatment or vaccine yet, the goal is primarily symptomatic relief for those affected and preventive for those at risk. Most countries have curtailed the spread of COVID-19 through measures such as lockdowns, social distancing and voluntary self-isolation. Although necessary, such measures and the disease itself may have an adverse impact on mental health. In view of research from previous pandemic crisis, it is known that such situations are likely to increase stress levels and have negative psychiatric effects. The impact is likely to be felt by the general public, sufferers of COVID-19, their families and friends, persons with pre-existing mental health conditions and healthcare workers. COVID pandemic related psychological distress in the general public, including symptoms of anxiety and depression, is associated with alterations in immune function, including an elevated risk of viral respiratory tract infection.